Acute Renal Replacement Therapy in Pediatrics. (1st June 2011) - Basu, Rajit K.; Wheeler, Derek S.; Goldstein, Stuart; Doughty, Lesley
Abstract : Acute kidney injury (AKI) independently increases morbidity and mortality in children admitted to the hospital. Renal replacement therapy (RRT) is an essential therapy in the setting of AKI and fluid overload. The decision to initiate RRT is complex and often complicated by concerns related to patient hemodynamic and thermodynamic instability. The choice of which RRT modality to use depends on numerous criteria that are both patient and treatment center specific. Surprisingly, despite decades of use, no randomized, controlled trial study involving RRT in pediatrics has been performed. Because of these factors, clear-cut consensus is lacking regarding key questions surrounding RRT delivery. In this paper, we will summarize existing data concerning RRT use in children. We discuss the major modalities and the data-driven specifics of each, followed by controversies in RRT. As no standard of care is in widespread use for RRT in AKI or in multiorgan disease, we conclude in this paper that prospective studies of RRT are needed to identify best practice guidelines.